Identifying human phenotype terms in text using a machine learning approach - Lobo, Manuel Stapleton Garcia de Vasconcelos (2017)
Tese de mestrado, Bioinformática e Biologia Computacional (Bioinformática) Universidade de Lisboa, Faculdade de Ciências, 2017